The hidden universe : adventures in biodiversity - Antonelli, Alexandre (Witness Books, 2022)
This brief, lucid book by the Director of Science at Royal Botanical Gardens takes you on an unforgettable tour of the natural world, showing how biodiversity - the rich variety of life in the world and in our own backyards - provides both the source and the salvation of our existence. Combining inspiration stories and the latest scientific research, Alex Antonelli reveals the wonders of biodiversity at a genetic, species and ecosystem level - what it is, how it works, and why it's the most important tool in our battle against climate change.
Keywords: biodiversiteetti; luonnon monimuotoisuus; lajit; ekosysteemit (ekologia); hyöty; uhat; ratkaisut (vastaukset); luontokato; luonnonsuojelu; luonnonhistoria